2016
DOI: 10.1590/0102-33062016abb0112
|View full text |Cite
|
Sign up to set email alerts
|

Stamen morphoanatomy of Dyckia Schult.f. (Bromeliaceae, Pitcairnioideae) species: new data for taxonomic use

Abstract: Th is study presents a morphoanatomical analysis of Dyckia ibicuiensis, D. polyclada and D. racinae stamens. Flowers at anthesis were desiccated and their stamens were processed using common microtechniques for light microscopic analysis. Morphologically, the androecium in these species is diff erentiated by the disposition of the stamens around the gynoecium and by general anther characteristics. Included stamens, with antesepalous fi laments diff erent from those of the antepetalous, anthers in a radial disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(29 reference statements)
4
2
0
Order By: Relevance
“…These characteristic thickenings of the endothecium cell walls found in the present study in R. idaeus and described in the literature for other taxa determine the correct mechanism of anther dehiscence [29,30,89]. Endothecium wall thickenings composed of cellulose and lignin are formed after the phase of differentiation of anther cell layers, and this process is strictly dependent on auxins and jasmonic acid [29,98].…”
Section: Structure Of Epidermis and Endothecium Cellssupporting
confidence: 56%
See 1 more Smart Citation
“…These characteristic thickenings of the endothecium cell walls found in the present study in R. idaeus and described in the literature for other taxa determine the correct mechanism of anther dehiscence [29,30,89]. Endothecium wall thickenings composed of cellulose and lignin are formed after the phase of differentiation of anther cell layers, and this process is strictly dependent on auxins and jasmonic acid [29,98].…”
Section: Structure Of Epidermis and Endothecium Cellssupporting
confidence: 56%
“…In the epidermis cells of the red raspberry stamens, we confirmed the presence of a thick outer cell wall with perpendicular elevations corresponding to cuticle striae or arranged obliquely near the anticlinal wall. The present study and literature data showed that the cuticle exhibited a homogeneously distributed lamellar cuticle proper band and the outer and inner reticulate cuticular layers [87][88][89]. The epidermal wall was thickened and cutinized.…”
Section: Structure Of Epidermis and Endothecium Cellssupporting
confidence: 56%
“…Thus, while there are no similar studies in species related to D. polyclada, there may be peculiarities in the events of pollination in this species, due to occlusion of the corolla, as well as the distinct configuration of the androecium, features that may allow more inferences, not only of a reproductive nature, but also taxonomic, if assessed in other species. As for the relative position of the stamens and stigma in relation to the corolla, the morphometric data of the present study suggest that the exserted stigma in D. polyclada is due to the long style, however the exsertion of the stamens is not directly related to the relative size of the filament, since D. ibicuiensis presented the greatest values for this measure, but has included stamens, as was also observed by Carvalho et al (2016). We underline, however, that the exsertion in D. polyclada occurs after anthesis, due to the apparent increase in the lengths of the androecium and gynoecium, a common phenomenon in angiosperms, which can occur by cellular elongation, or even by the presence of intercalary meristems at the base of these organs (Greyson 1994).…”
Section: Discussionsupporting
confidence: 80%
“…The androecium, which in this study was found to be one of the most important whorls for comparative purposes, was treated in detail by Carvalho et al (2016), in an anatomical and morphological analysis. Among the most important features described by the authors, the different types of fibrous thickenings found in endothecium are important as they allowed the establishment of a relationship between D. racinae and D. ibicuiensis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation